An Contemplation on Virtual Memory Management Techniques of Virtual Machines - A. Sindhuja, S. Malathi (International Journal of Advanced Science and Technology, 2020)
Now a days many new technology are overwhelming. There by many organization and institution are benefited. Software developed in this new technological generation requires more memory space during application runs, when compared to existing technologies therefore it is difficult to install these new application in lower version systems.Though Data-center are established to overcome this problem where installation and maintenance cost is very high and not suitable for small organization or institutions. To vanquish these issues virtual environment as been created to manage the memory requirement in an dwindling way. Memory resource isn’t easy to use and share flexibly in that each virtual machine has its memory size set by Software initiale. Hence the usage of memory resources as been analyzed with an effective memory management techinquessuch as memory swapper ,virtual memory migration and memory ballooning etc.In this paper ,we going to combine the virtual memory monitoring tool self e method along with the three phase optimization method to crucially improves the overall performance hence it is very efficient to trace the access of memory without any overhead or performance degradation and it also improve an significantly reduces the search process and imposes overhead occurs in live migration.